The thermoacoustic instability in a stratified swirl burner and its passive control by using a slope confinement. (15th March 2020) - Song, Heng; Lin, Yuzhen; Han, Xiao; Yang, Dong; Zhang, Chi; Sung, Chih-Jen
Highlights: Mechanisms of thermoacoustic oscillations in the dump confinement are elucidated. A passive control method is proposed by using the slope confinement. This method suppresses the flame front wrinkling and flame root angle fluctuation. The slope confinement reduces the gain of the flame transfer function. This reduction of the gain enhances the system thermoacoustic stability.